A Study on the globalization of Philip Morris - Kim, Moon Ki (KDI School, 2000)
With the trend of free trading and opening of the market, market leading multinational tobacco companies are accelerating their moves to take advantageous position in the global tobacco market. From 1987, after the opening of the Korean cigarette market, all the major cigarette brands of multinational tobacco companies came into the Korean cigarette market and have been competing fiercely. Korean Tobacco and Ginseng Corporation (KT&G) which had enjoyed monopolistic status is losing its market share. In Korea, the cigarette market has matured and there is little room to grow in the domestic market. Outside of Korea, there are many growing tobacco markets in the world, and KT&G's future growth will can only come from international sales. This study has examined Philip Morris Companies INC's (PM) successful case of globalization in the tobacco industry. From this study, PM's key success factors of successful globalization was found. This study shows that PM's successful globalization has accomplished by superior tobacco industry knowledge, global Marlboro franchise, strong portfolio of American Heritage Brands, vast manufacturing, sales, and distribution infrastructure. With these strengths, Philip Morris generates substantial excess free cash flow and is constantly in search of investment vehicles. For globalization, KT&G has to develop technology and reduce cost for achieving price competitiveness, and it has to do licensing, joint-venturing or strategic alliances in the areas of product development, manufacturing, and marketing outside of Korea.
Thesis(Master) --KDI School:Master of Business Administration,2000